Return On Assets, Current Ratio,Net Profit Margin, Total Asset Turnover Berpengaruh Terhadap Perkembangan Laba Pada Industri Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2015- 2019 - Williana Silviani; Rosdiana Panjaitan; Sally Angelika Hutagalung; Tetty Tiurma Uli Sipahutar (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to test whether Return On Assets, Current Ratio, Net Profit Margin, Total Asset Turnover have an effect on the growth of profits listed on the Indonesia Stock Exchange. This research is a type of quantitative descriptive research, which uses data from 135 large and small trading sector manufacturing companies listed on the Indonesia Stock Exchange. Partially, the variables of return on assets, current ratio and total asset turnover have no effect on profit growth. Meanwhile, the net profit margin variable has a positive effect on profit growth. And simultaneously, the independent variable has no effect on the profit growth variable. The sampling method used in this research is purposive sampling. The method in this research is descriptive analysis method and multiple linear regression analysis method. Keywords: Return On Assets, Current Ratio, Net Profit Margin, Total Asset Turnover, Profit Growth